Costi e bisogni sanitari degli anziani non autosufficienti presso le strutture residenziali: strategie e interventi per una popolazione che invecchia - Moro, Marta; Salvato, Chiara; Terrazzani, Gianni; Serraglia, Donatella; Saramin, Cristina; Giusti, Pietro; Chinellato, Alessandro (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
CONTEXT: The number of elderly is constantly increasing in the western world and many of this people spend the last years of their life in a nursing home with physical and/or mental disabilities. OBJECTIVE: To estimate the Health Service resource and direct costs for Community Residential Care (CRC) disabled elderly people. METHODS: A retrospective observational study was conducted between January 2002 and December 2002 among all CRC (23 CRC and 1665 disabled residential elderly population REP) of the Local Health Authority n° 9 of Treviso. For each CRC data regarding patients, hospitalisation, clinical analysis, general practitioner and hospital medical doctor assistance, drug utilisation were collected and analysed. RESULTS: Males were 27% and female 73% with an average age 78 and 86 years old respectively. Frequency of hospitalisation, clinical analysis and drug utilisation vary widely between the CRC and an inverse correlation is observed between cost of hospitalisation and drug plus clinical analysis. The first causes of hospitalisation are pneumonia 7.2% and cardiovascular disease 4.9% both considered preventable cause of hospitalisation. Regarding the drug consumption analysis enalapril, furosemide, omeprazole are the most used molecules with a consumption of 308, 185, 166 DDD/1000 REP/die; systemic antibiotics are the more expensive drugs with a cost of 0.3 euro/REP/die. Unexpected laxatives consumption is lower than data from literature with a 17% of the total REP exposed. Finally average annually cost for a REP in CRC is 16,445 euros and beside the direct sponsor of local health authority to the CRC hospitalisations cost are the most important (899 euros) while drugs, medical assistance and sanitary material cost are similar with an annual cost of 530 euros, 492 euros, 450 euros respectively. Hypnotic and anxiolytic consumption appear to be correct with literature data with about 30% population exposed. CONCLUSION: Females are disabled about 10 years after males, many hospitalisation could be avoided with correct sanitary programs and finally and inverse correlation of drug consumption and hospitalisation is observed.